Pelaksanaan Putusan Pengadilan Agama terhadap Nafkah Anak Pasca Putusnya Perkawinan PNS: (Dalam Prespektif Hukum Nasional dan Hukum Islam) (Jurnal Sosial Humaniora dan Pendidikan, 2025)
Support is the responsibility of a father (husband) toward his children until they become adults and are capable of supporting themselves. However, if the child has reached legal age but is unable to work due to illness or other limitations, the father remains obligated to provide support. In the Malang Regency Religious Court, there have been several cases where Civil Servants failed to comply with court decisions regarding child support after divorce. This issue typically arises when the ex-wife files a lawsuit because the ex-husband refuses to implement the court’s decision. Some cases also involve appeals filed by the ex-husband who disagrees with the judge’s considerations in determining the amount of support. Such situations significantly affect the child’s well-being and development.This study aims to examine the legal basis and judicial considerations used by the Malang Regency Religious Court in determining child support obligations for Civil Servants, the legal remedies available when the decision is not enforced, and an analysis from the perspective of Islamic law. The research employs a qualitative method using an empirical juridical approach. Data were collected through field research, including primary data (interviews and observations) and secondary data (documents and literature).The study concludes that the father, even after divorce, is still legally and morally responsible for the child's welfare. Obstacles to fulfilling this obligation often stem from the father's new relationships or ongoing conflicts between former spouses, which negatively impact the child's right to financial support.